Tinjauan Tentang Faktor-Faktor Yang Mempengaruhi Minat Berkunjung Kembali Wisatawan (Studi Kasus Taman Wisata Boon Pring Desa Sananrejo Kecamatan Turen Kabupaten Malang) - Sahrul Hurum, Alafin Ibnu Syifa’; Wahono, Budi; Mawardi, M Cholid (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the extent of development of the Boon Pring tourist park and the factors that influence tourists to return to the Boon Pring Sananrejo Turen tourist park. The data mining techniques used in this research are through interviews, observation and documentation. And the data analysis in this research is qualitative data analysis is inductive.The research results show that tourism development in Boon Pring is carried out in the form of adding various tourist attractions and activities. Tourist infrastructure to the Boon Pring area includes transportation, road networks and signs pointing to majors in good condition. Boon Pring tourist facilities (facilities) consist of 8 bathrooms/toilets, stalls, gazebos spread throughout the Boon Pring area, a large parking area, and there are 20 homestays with a total of 30 rooms. In terms of management/infrastructure, available electrical energy sources from the PLN network, including monitoring and security facilities, there are written prohibitions on what not to do while in the Boon Pring area. The management even prepared several officers to go around the bamboo forest to ensure security. In the field of community, environmental and cultural development, in the form of strengthening and educating tourism awareness through village clean-up activities. Availability of facilities, maintenance of cleanliness and guaranteed security are factors that can increase tourists' interest in returning to the Boon Pring tourist attraction. Keywords: Interest In Visiting, Facilities, Cleanliness, Security